The Use of Garlic Extract (Allium Sativum) as an Alternative to Recover Blood Pressure and Malodialdehyde (MDA) Levels on Mothers (Post-Partum) - Else Sri Rahayu (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Complication on post-partum is a part of 80% which causes maternal mortality as stated by World Health Organization. Hypertension case during childbed tends to increase. To prevent, maintain, and cure herbal supports security and health effect improvement. The side effect is lesser than conventional medicine. Garlic supplementation is correlated to blood pressure digression significantly on hypertension patient. Malodialdehyde (MDA) is production of lipid peroxide which contains aldehyde substance. It describes oxidative stress level as lipid peroxide biomarkers which can be prevented by antioxidant. Objective This research proved the administration of garlic extract could influence blood pressure recovery and MDA level of post-partum mothers. Method Quasi experimental with non-equivalent control group design took 28 participants as sample. They were divided into 2 groups consisting of 14 participants controlled by POR, 14 intervention participants with POR administered by garlic extract 681.6 mg. The sample was consecutive sampling. Data analysis used mann whitney statistic test continued by friedman test and Post Hoc Wilcoxon. Findings Blood pressure digressions of pre-post intervention average scores of 2 groups showed the first systolic measurement and third diastolic measurement. Systolic and diastolic blood pressure showed p value 0.000 and MDA level with p value 0.705. The total of blood pressure average of systolic group was 23.21 mmHg with p value 0.000. The diastolic was 7.22 mmHg with p value 0.016. The MDA showed lover score –(50.64 nmol/mL) p value 0.705. Conclusion and Recommendation There was influence of garlic extract to blood pressure and there was no influence of garlic extract to MDA level.